Influence of reduction quality on functional outcome and quality of life in treatment of tibial plafond fractures: a retrospective cohort study - Privalov, Maxim; Keil, Holger; Swartman, Benedict; Beisemann, Nils; Franke, Jochen; Grützner, Paul Alfred; Vetter, Sven Y. (BMC musculoskeletal disorders, 2019)
The aim of the study was to evaluate the impact of reduction quality, using intraoperative 3D imaging, on quality of life and functional outcome in the operative treatment of tibial plafond fractures.
Gesehen am 16.12.2019